Огляд можливостей застосування засобів штучного інтелекту щодо процедур тестування програмного забезпечення інфокомунікаційних систем - Прохоров, О. І.; Бондар, Д. В. (ХНУРЕ, 2025)
Intensive development of modern infocommunication systems requires high quality testing to ensure efficiency, security and productivity. The main types of testing are functional, load, security testing, globalization and automated testing. The use of artificial intelligence significantly improves the quality of testing, reduces costs and speeds up processes. Currently, there are AI tools: ChatGPT, Gemini, Mistral and Claude3, which demonstrate quite powerful capabilities in log analysis, test scenario creation and test automation. The most effective for testing infocommunication systems is ChatGPT, which provides the best support for test scenario generation and process automation.
Keywords: тестування програмного забезпечення ін; застосування штучного інтелекту